A reflective exercise on the issue of sexuality in the view of undergraduate nursing students: evaluating the process - Graciela Dutra Sehnem; Maria de Lourdes Denardin Budó; Lúcia Beatriz Ressel; Emanoeli Büttenbender (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
This paper presents an outline of the field research using a qualitative approach: "Sexuality as a cultural element: signification and resignification in the formation of nurses". This study involved undergraduate nursing students from a Federal Public University in the south of Brazil, and was carried out through a reflective exercise on sexuality based on a focal group technique, emphasizing the cultural perspective that involves this theme. This work highlights the evaluation process of this experience. The evaluations revealed several positive aspects provided by this exercise, such as the extension of the concept of sexuality, self-knowledge, a personal awakening of interest in humanized care, ambiguity and sharing feelings. The evaluation of the research exercise indicated the necessity to discuss the concept of sexuality in the formation of undergraduate nursing students, enabling the creation of spaces propitious to the manifestations mentioned above.